Family Empowerment Model Based on Madurese Social and Cultural Structures to Prevent Stunting - Suryaningsih, Suryaningsih; Fitriah, Fitriah; Rodiyatun, Rodiyatun; Hendriyani, Feftin; Haris, Mustofa (Health Dynamics, 2025)
Background: Bangkalan district has the highest incidence of stunting in East Java. Various efforts have been made to accelerate the reduction of stunting, but maximum results have not been achieved. This study aimed to determine the impact of family empowerment based on Madura sociocultural structures on the ability to prevent stunting. Methods: This study used a cross-sectional design with a population of families with school-aged children in PAUD, Regency area of Bangkalan, with a sample of 280 individuals drawn by stratified random sampling. Data analysis was performed using SEM. Results: The results showed that the Madurese family culture and social structure were built on religious, kinship, and economic interest indicators. Family empowerment, with aspects of family structural strength, family functioning, and family values, influences the family's ability to prevent growth retardation. Family empowerment in stunting prevention is strongly influenced by the culture and social structure of the Madura family. Indicators of stunting prevention skills include the ability to meet family nutrition, fertility management, growth and development monitoring, personal and environmental hygiene patterns, and family capacity to modify the environment. The more power a family has, the more impact it has on their ability to prevent stunting. Conclusion: Stunting based on Madhura culture can be achieved through the integrative implementation of stunting. Local government organizations involve informal community figures